Substantiation of the technology for integrating the physical and technical preparation of swimmers aged 11–14 years - Malinovskiy, M.S.; Arishin, A.V.; Pogrebnoy, A.I. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the technology for integrating the physical and technical preparation of swimmers aged 11–14 years. Methods and structure of the study. The scientific work used the analysis of literature data; various approaches to the development of physical qualities and technical preparedness were studied; the results of the authors’ own long-term observations, conducted on a contingent of 124 swimmers aged 11–14 years, were generalized. The study included the application of methods of computer video analysis, testing, hardware diagnostics (Swim Force Test, VASA Swim Ergometer), design, modeling, as well as methods of mathematical statistics. The data processing was carried out using correlation, regression, and ROC analysis. Results and conclusions. The following components of the technology for integrating the physical and technical preparation of swimmers are proposed: conceptual, content-related, and procedural, based on the principles of level-based continuity, integrative systematicity, complementarity, and synergism. The application of special methods (conjugation, level-based construction, technique stabilization, complementation of means, stress impacts) and selected exercises, including those on simulators, makes it possible to ensure the conjugated development of physical qualities and swimming technique, creating conditions for the effective transfer of fitness into the structure of the competitive action.